Safety of administration of BNT162b2 mRNA (Pfizer‐BioNTech) COVID‐19 vaccine in youths and young adults with a history of acute lymphoblastic leukemia and allergy to PEG‐asparaginase. Issue 11 (16th August 2021) - Mark, Catherine; Gupta, Sumit; Punnett, Angela; Upton, Julia; Orkin, Julia; Atkinson, Adelle; Clarke, Lindsay; Heisey, Alice; McGovern, Christine; Alexander, Sarah
Abstract: Vaccinationis a critical tool in the prevention of COVID‐19 infection for individuals and for communities. The mRNA vaccines contain polyethylene glycol (PEG) as a stabilizer. Currently, in North America, only the BNT162b2 (Pfizer‐BioNTech) mRNA vaccine is approved for individuals aged 12–17. Most patients treated with contemporary regimens for acute lymphoblastic leukemia receive PEG‐asparaginase (PEG‐ASNase) and 10%–30% will develop allergic reactions. Optimizing access and safety for vaccine administration for these patients is critical. This report describes a process developed to support COVID vaccination in a cohort of adolescents and young adults with a history of PEG‐ASNase allergy.